Gait deviations of the uninvolved limb and their significance in unilateral cerebral palsy - Tsitlakidis, Stefanos; Campos, Sarah; Mick, Paul; Doll, Julian; Hagmann, Sébastien; Renkawitz, Tobias; Götze, Marco; Hetto, Pit (Symmetry, 2023)
Little is known about the impact of the impaired limb on the uninvolved side, which might influence the overall functional outcome in individuals with unilateral cerebral palsy (CP). The objective of this work was to perform an assessment considering the kinematics/joint moments and ground reaction forces (GRFs). Eighty-nine individuals with unilateral CP were included and classified according to their functional impairment. Level-specific differences according to the Gross Motor Function Classification System (GMFCS), including pelvic and trunk movements, were analyzed using instrumented 3D gait analysis (IGA). Anterior trunk and pelvic tilt, trunk lean/pelvic obliquity, pelvic internal rotation, hip adduction, and external hip rotation, as well as pronounced flexion (ankle dorsiflexion), at all joint levels were significant kinematic alterations. Concerning joint moments, the most remarkable alterations were hip and ankle flexion, hip abduction, knee varus/valgus, and transversal joint moments at all levels (external rotation moments in particular). The most remarkable differences between GMFCS levels were at proximal segments. The kinematics and joint moments of the sound limb in patients with unilateral CP differ significantly from those of healthy individuals—partially concomitant to those of the involved side or as motor strategies to compensate for transversal malalignment and leg-length discrepancies (LLDs). GRF showed almost identical patterns between GMFCS levels I and II, indicating an unloading of the involved limb. Compensatory motor strategies of the sound limb do not influence functional outcomes.